Purification of IgG and albumin from human plasma by aqueous two phase system fractionation - Vargas Arroyo, Mariángela (2012)
The current shortages in human plasma products at global levels justify the development of new, cost effective plasma fractionation methods. We have developed a fractionation process to obtain immunoglobulin G (IgG) and albumin-enriched fractions based on polymer-salt aqueous two phase system (ATPS). A small-scale (0.02 L) ATPS composed of polyethyleneglycol 3350 (PEG), potassium phosphate and sodium chloride, at pH 6.1, was evaluated and subjected to 50-fold scale-up (1 L). Further purification of the fractions was performed using caprylic acid precipitation and ion exchange chromatography. Similar yield and purity were obtained at both small and large scales. IgG precipitated in the PEG rich upper phase at 83% recovery and 2.75-fold purification factor. An 81% pure albumin fraction was obtained in the salt rich bottom phase with a 91% yield. After polishing, IgG was obtained at a recovery of 70% and a purity of 92%. Corresponding values for albumin were 91% and 90%. This IgG and albumin fractionation technology deserves further evaluation as it may represent a potential alternative to conventional plasma fractionation methods